Children and Young Adults Who Received Tracheostomies or Were Initiated on Long-Term Ventilation in PICUs*. Issue 8 (August 2016) - Edwards, Jeffrey D.; Houtrow, Amy J.; Lucas, Adam R.; Miller, Rachel L.; Keens, Thomas G.; Panitch, Howard B.; Dudley, R. Adams
Abstract : Objectives: To characterize patients who received tracheostomies for airway compromise or were initiated on long-term ventilation for chronic respiratory failure in PICUs and to examine variation in the incidence of initiation, patient characteristics, and modalities across sites. Design: Retrospective cross-sectional analysis. Settings: Seventy-three North American PICUs that participated in the Virtual Pediatric Systems, LLC. Patients: PICU patients admitted between 2009 and 2011. Interventions: None. Measurements and Main Results: Among 115, 437 PICU patients, 1.8% received a tracheostomy or were initiated on long-term ventilation; 1, 034 received a tracheostomy only, 717 were initiated on invasive ventilation, and 381 were initiated on noninvasive ventilation. Ninety percent had substantial chronic conditions and comorbidities, including more than 50% with moderate or worse cerebral disability upon discharge. Seven percent were initiated after a catastrophic injury/event. Across sites, there was variation in incidence of tracheotomy and initiation of long-term ventilation, ranging from 0% to 4.6%. There also was variation in patient characteristics, time to tracheotomy, number of extubations prior to tracheostomy, and the use of invasive ventilation versus noninvasive ventilation. Conclusions: Although the PICU incidence of initiation of tracheostomies and long-term ventilation was relatively uncommon, it suggests that thousands of children and young adults receive these interventions each year in North American PICUs. The majority of them have conditions and comorbidities that impose on-going care needs, beyond those required by artificial airways and long-term ventilation themselves. Abstract : Supplemental Digital Content is available in the text.